HPV Status Determines the Efficacy of Adjuvant Chemotherapy With S-1, an Oral Fluorouracil Prodrug, in Oropharyngeal Cancer. (May 2015) - Wakisaka, Naohiro; Yoshida, Shinya; Kondo, Satoru; Kita, Makiko; Endo, Kazuhira; Tsuji, Akira; Murono, Shigeyuki; Muramatsu, Masamichi; Yoshizaki, Tomokazu
Objectives: A subgroup of oropharyngeal squamous cell carcinoma (OPC) is infected with high-risk human papillomavirus (HPV). The object of this study is to evaluate the efficacy of adjuvant chemotherapy with S-1, an oral 5-fluorouracil prodrug, on survival of patients with OPC according to HPV status. Methods: Among OPC patients of stage III or IV who received definitive treatment from 1998 to 2008, 38 who were confirmed tumor-free after primary treatment were analyzed. Before 2003, none of the patients received S-1 adjuvant chemotherapy (S-1(-)-group); however, all patients who were eligible were administered S-1 (S-1(+)-group) after 2003. The expression of thymidylate synthase (TYMS) involved in 5-FU metabolism was also examined in protein and mRNA levels. Results: Although there was a trend to disease-free and overall survival benefit in HPV-negative patients with S-1, it did not achieve statistical significance ( P = .082 and P = .065, respectively). For the HPV-positive patients, the survivals were similar with or without S-1 administration. TYMS-expression in HPV-positive OPC tissues was significantly higher than in HPV-negative ones in both protein and mRNA levels ( P = .0489 and P = .0446, respectively). Conclusion: The current study provides a rationale to plan a randomized trial to compare the efficacy of S-1 according to the HPV status in OPCs.